CLINICAL FEATURES OF PROSTHODONTIC TREATMENT IN PATIENTS WITH COMPLETE EDENTULISM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Treatment of patients with complete edentulism presents significant clinical challenges due to anatomical, functional, and psychological factors. This review analyzes clinical considerations influencing prosthodontic outcomes. Literature from 2010–2025 was reviewed focusing on ridge anatomy, neuromuscular adaptation, and systemic factors. Successful treatment depends on individualized assessment and careful prosthetic planning.